Laboratory Research on Fracture-Supported Shielding Temporary Plugging Drill-In Fluid for Fractured and Fracture-Pore Type Reservoirs - Dawei Liu; Yili Kang; Quanwen Liu; Dengsheng Lei; Bo Zhang (Journal of Chemistry)
Based on fractures stress sensitivity, this paper experimentally studies fracture-supported shielding temporary plugging drill-in fluid (FSDIF) in order to protect fractured and fracture-pore type formation. Experimental results show the FSDIF was better than the CDIF for protecting fractured and fracture-pore type reservoir and the FSDIF temporary plugging rate was above 99%, temporary plugging ring strength was greater than 15 MPa, and return permeability was 91.35% and 120.83% before and after acidizing, respectively. The reasons for the better reservoir protection effect were analyzed. Theoretical and experiment studies conducted indicated that the FSDIF contained acid-soluble and non-acid-soluble temporary shielding agents; non-acid-soluble temporary shielding agents had high hardness and temporary plugging particles size was matched to the formation fracture width and pore throat size.